Perspectives on Health: Working with Communities as Cultural Anthropologists and Bioarchaeologists - Purhcase, Samantha L. (Engaged Scholar Journal, 2020)
The anthropological study of health has always been an integral part of the discipline. With the development of cultural anthropology and physical anthropology (specifically, bioarchaeology) in the nineteenth century came different theories and methodologies concerning the study and definition of communities. Still today, cultural anthropology and bioarchaeology share the same broad goals of exploring the evolving relationships between experiences of health and the community, culture, and environment (being natural, domestic, political, and social). That cultural anthropologists study extant cultures and bioarchaeologists do not has necessitated the evolution of different methodological practices. Here, I explore some of the differences between these two sub-disciplines: their differing notions of community, how they engage with communities, and the relevance of their work to the communities they study. I contextualize this analysis with a short discussion of the sub-disciplines’ co-evolution and ground it with examples from my research with middle Holocene Siberian, Russian Federation, and Anglo-Saxon to Post-Industrial British communities.